Growth Performance, Survival Rate, and Water Quality in an Aquaculture System Using Different Feeding Strategies for Juveniles of Nile Tilapia (Oreochromis niloticus) - Gustavo Fonseca; Emerson Machado De Carvalho; Dagon Manoel Ribeiro (Aquatic Sciences and Engineering)
Aquaculture is a rapidly growing industry worldwide, with Nile tilapia (Oreochromis niloticus) being one of the most intensively farmed fish species. This study aimed to evaluate the growth performance and water quality parameters in different culture systems for Nile tilapia. Six treatments were tested, including variations in feed type (commercial or microalgae), aeration, and their combinations. The results showed that the presence of commercial feed and aeration (T2) resulted in the highest weight gain and specific growth rates, while treatments without commercial feed showed lower growth performance. The addition of microalgae supplementation did not significantly improve growth compared to commercial feed alone. Water quality parameters, particularly nitrite levels and dissolved oxygen, played crucial roles in the production of tilapia. It was observed that high nitrite levels were associated with decreased growth and survival rates. Proper monitoring and management of water quality, including nitrite levels and dissolved oxygen, are essential to ensure the survival and growth of tilapia in aquaculture systems. These findings highlight the importance of implementing sustainable practices and appropriate feeding strategies to optimize the growth and well-being of farmed tilapia while minimizing environmental impacts.